Penerapan model problem based learning berbantuan media audiovisual pada pembelajaran IPS kelas V Sekolah Dasar - Nila Ariyanti; Tio Gusti Satria; Armi Yuneti (IKIP Siliwangi, 2026)
Abstrak This study aims to measure the learning outcomes of fifth-grade students at Trans Muara Megang Public Elementary School after implementing a problem-based learning model assisted by audiovisual media. This study is a quasi-experimental study with a one-group pretest-posttest design. The subjects of this study were 21 fifth-grade students at Trans Muara Megang Public Elementary School. Data collection techniques were carried out by administering tests to students and documenting the results. The research findings indicate that there was an improvement in students' learning outcomes after the implementation of the PBL model assisted by audiovisual media in the social studies subject matter on the causes of changes in natural conditions and efforts to address them. Based on the data analysis, the average pretest score was 58.82 and the average post-test score was 78.33, indicating an increase in student learning outcomes of approximately 19.51 after the implementation of the PBL model assisted by audiovisual media. Based on the z-test analysis, the value of Zcount ≥ Ztable was obtained, namely 6.59 ≥ 1.64. Therefore, it can be concluded that the learning outcomes of Grade V IPS students after the implementation of the PBL model assisted by audiovisual media were significantly improved. Keywords: Learning Outcomes, PBL,Social Studies Penelitian ini bertujuan untuk untuk mengukur ketuntasan hasil belajar IPS peserta didik kelas V SD Negeri Trans Muara Megang setelah penerapan model problem based learning berbantuan media audiovisual. Penelitian ini merupakan penelitian eksperimen semu dengan desain one group pretest - posttest. Subjek penelitian ini adalah peserta didik kelas V SD Negeri Trans Muara Megang sebanyak 21 orang peserta didik. Teknik pengumpulan data dilakukan dengan memberikan soal tes kepada peserta didik dan dokumentasi. Hasil penelitian menunjukkan bahwa terdapat peningkatan hasil belajar peserta didik setelah diterapkannya model PBL berbantuan media audiovisual pada mata pelajaran IPS materi faktor penyebab perubahan kondisi alam dan upaya mengatasinya. Berdasarkan analisis data yang telah dilakukan, rata rata skor pre-test yaitu sebesar 58,82 dan rata-rata skor post-test sebesar 78,33 sehingga terdapat peningkatan hasil belajar peserta didik sekitar 19,51 setelah diterapkannya model PBL berbantuan media audiovisual. Berdasarkan analisis uji-z, diperoleh nilai Zhitung ≥ Ztabel, yaitu 6,59 ≥ 1,64. Sehingga dapat disimpulkan bahwa hasil belajar IPS Kelas V SD Negeri Trans Muara Megang setelah diterapkan model PBL berbantuan media audiovisual signifikan tuntas. Kata Kunci: Hasil Belajar, PBL, IPS